Analysis of Environmental Degradation and Its Determinants in Nigeria: New Evidence from ARDL and Causality Approaches - ADEKUNLE, Wasiu; OMO-IKIRODAH, Beatrice. O.; COLLINS, Olutosin; ADENIYI, Andrew; BAGUDO, Abubakar; MOSOBALAJE, Risikat O.; OLADEPO, Safiyyah (Theoretical and Practical Research in Economic Fields; Vol 13 No 1 (2022): TPREF, Volume XIII, Issue 1(25), Summer 2022, 2022)
This paper extends the previous studies to re-examine the functional relations and causal links between environmental degradation and its possible determinants in Nigeria, covering 1977 to 2015. With the aid of ARDL model estimation, the study found a positive relationship between economic growth and environmental degradation (measured by carbon emission). A positive relation was also established between energy consumption and carbon emission. Similarly, this study reported a positive relationship between transport services in the import and export sectors and carbon emission. Through the Granger causality test, the study established a unidirectional causality running from carbon emission to economic growth. Similarly, there was a unidirectional causality running from economic growth to transport services in the export sector. Based on these findings, there is an increasing need for the authorities to regulate economic activities that directly and indirectly contribute to systematic environmental degradation in Nigeria.